Using Crop Models and Climate Forecasts to Aid in Peanut Crop Insurance Decisions - Clyde W. Fraisse; James L. Novak; Axel Garcia y Garcia; James W. Jones; Charles M. Brown; Gerrit Hoogenboom (EDIS)
Crop insurance is one of the strategies producers can use to reduce risk of income loss due to climate variability. The best approach for reducing risks involves a combination of crop insurance with a pre-harvest marketing plan that includes strategies like hedging and forward contracting. A producer's choice among strategies is often complicated when both price and yield risk are present. However, about 69% of crop failures in the U.S. are because of either drought or excessive moisture (Ibarra and Hewitt, 1999). Are there options for a farmer to reduce these weather and climate-based risks, and can a grower take advantage of climate forecast information to decide about insurance levels? This paper explores this idea for peanuts and provides examples of how to use crop growth simulation models in combination with climate forecasts to decide about coverage levels. This document is CIR 1468, one of a series of the Agricultural and Biological Engineering Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published July 2005. Reviewed: September 2008.